High intraperitoneal interleukin-6 levels predict ultrafiltration (UF) insufficiency in peritoneal dialysis patients: A prospective cohort study - Song, Qianhui; Yang, Xiaoxiao; Shi, Yuanyuan; Yan, Hao; Yu, Zanzhe; Li, Zhenyuan; Yuan, Jiangzi; Ni, Zhaohui; Gu, Leyi; Fang, Wei (Frontiers in Medicine, 2022)
Introduction: UF insufficiency is a major limitation in PD efficiency and sustainability. Our study object to investigate the efficacy of intraperitoneal inflammation marker, IL-6 level as a predictor of UF insufficiency in continuous ambulatory peritoneal dialysis (CAPD) patients. Methods: Stable prevalent CAPD patients were enrolled in this prospective study. IL-6 concentration in the overnight effluent was determined and expressed as the IL-6 appearance rate (IL-6 AR). Patients were divided into 2 groups according to the median of IL-6 AR and prospectively followed up until death, transfer to permanent HD, recovery of renal function, kidney transplantation, transfer to other centers, lost to follow-up or to the end of study (January 31, 2021). Factors associated with UF capacity as well as dialysate IL-6 AR were assessed by multivariable linear regression. Cox proportional hazards model was used to examine the association between dialysate IL-6 AR and UF insufficiency. Results: A total of 291 PD patients were enrolled, including 148 males (51%) with a mean age of 56.6±14.1 years and a median PD duration of 33.4 (12.7-57.5) months. No correlation was found between dialysate IL-6 AR and UF capacity at baseline. PD duration was found positively correlated with baseline dialysate IL-6 AR, while 24h urine volume was negatively correlated with baseline dialysate IL-6 AR (P<0.05). By the end of study, UF insufficiency was observed in 56 (19.2%) patients. Patients in the high IL-6 AR group showed a significantly inferior UF insufficiency-free survival when compared with their counterparts in the low IL-6 AR group (P=0.001). In the multivariate Cox regression analysis, after adjusting for DM, previous peritonitis episode and 24h urine volume, higher baseline dialysate IL-6 AR (HR 3.639, 95% CI 1.776-7.456, P=0.002) were associated with an increased risk of UF insufficiency. The area under the ROC curve (AUC) for baseline IL-6 AR to predict UF insufficiency was 0.663 (95% CI, 0.580–0.746; P< 0.001). Conclusions: Our study suggested that the dialysate IL-6 AR could be a potential predictor of UF insufficiency in patients undergoing PD.